GERAKAN EDUKASI DALAM PENCEGAHAN STUNTING DAN PERILAKU ODF PADA MASYARAKAT DESA JAYALAKSANA - Juniati, Ainun; Akmalsyah Rahman, Rafi; Marlina, Selly; Sopandi, Andi; Irham, Irham (An-Nizam, 2023)
A clean environment is very important because it has a big impact on children's health and growth. Children's growth can also be disrupted due to a polluted environment. ODF behavior can be a factor in stunting in an area. Open Defecation Free (ODF) in Indonesia is still a problem, 33 out of 34 provinces in Indonesia are still not 100% verified as ODF, in Bekasi district itself there are still many areas that carry out ODF behavior and the reduction in stunting cases has not yet reached the target.This community service uses counseling and training methods.The aim of this research is to achieve "Zero Stunting and ODF" in order to build a cleaner and more advanced village. There are still places that need better village development, because most houses in Jayalaksana Village do not have proper sanitation or waste disposal, thereby polluting the water while the water is still used by local residents for washing. It can be concluded that this community service activity has a positive impact which can help residents in thinking and planning development.